2019
DOI: 10.1242/dev.176735
|View full text |Cite
|
Sign up to set email alerts
|

Yap/Taz-TEAD activity links mechanical cues to progenitor cell behavior during zebrafish hindbrain segmentation

Abstract: Cells perceive their microenvironment through chemical and physical cues. However, how the mechanical signals are interpreted during embryonic tissue deformation to result in specific cell behaviors is largely unknown. The Yap/Taz family of transcriptional co-activators has emerged as an important regulator of tissue growth and regeneration, responding to physical cues from the extracellular matrix, and to cell shape and actomyosin cytoskeletal changes. In this study, we demonstrate the role of Yap/Taz-TEAD ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 54 publications
11
64
0
Order By: Relevance
“…Recently, actomyosin and Yap-mediated mechanisms have also been shown to be essential for maintaining rhombomere boundaries in zebrafish (Calzolari et al, 2014.,Voltes et al, 2019. However, our analysis with F-actin reporters and active Yap signaling reporter did not reveal any involvement during MHB formation (supplementary Fig S2).…”
Section: Molecular Mechanisms Of Cell Sorting At the Mhbmentioning
confidence: 58%
“…Recently, actomyosin and Yap-mediated mechanisms have also been shown to be essential for maintaining rhombomere boundaries in zebrafish (Calzolari et al, 2014.,Voltes et al, 2019. However, our analysis with F-actin reporters and active Yap signaling reporter did not reveal any involvement during MHB formation (supplementary Fig S2).…”
Section: Molecular Mechanisms Of Cell Sorting At the Mhbmentioning
confidence: 58%
“…These complementary domains of ligands and receptors set up bidirectional signaling interactions that govern cell sorting and adhesion in the hindbrain. Experiments have revealed that the Eph‐ephrin signaling system has a key role in restricting mixing of cells between rhombomeres and in the formation of rhombomeres boundaries …”
Section: Introductionmentioning
confidence: 99%
“…Experiments have revealed that the Eph-ephrin signaling system has a key role in restricting mixing of cells between rhombomeres [63][64][65][66][67] and in the formation of rhombomeres boundaries. 46,[68][69][70][71][72] Early in initiation of the segmentation cascade, signals adjacent to neural tissue along with signals within the neural epithelium play important roles in regulating the establishment of rhombomeres. 2,3,7,38,47 However, the degree to which signaling between rhombomeres participates in regulating segmental identity during hindbrain development is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Forward signaling has a dominant role as it triggers strong repulsion (O’Neill et al, 2016; Rohani et al, 2011; Rohani et al, 2014; Taylor et al, 2017), but reverse signaling can also contribute (Wu et al, 2019). A further mechanism is important in epithelial tissues in which Eph receptor activation leads to actomyosin contraction that increases cortical tension at the interface (Calzolari et al, 2014; Cayuso et al, 2019; O’Neill et al, 2016; Voltes et al, 2019). This increase in cortical tension can drive cell segregation and act as a barrier to intermingling between Eph receptor and ephrin-expressing cells (Canty et al, 2017).…”
Section: Introductionmentioning
confidence: 99%